2018
DOI: 10.3389/fmicb.2018.03154
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Patterns of Resistance Among Helicobacter pylori Strains in South-Western Poland

Abstract: Treatment failure of Helicobacter pylori infection is caused mainly by progressive antibiotic resistance among H. pylori strains. In Poland, the prevalence of H. pylori strains resistant to metronidazole is higher than in other developed countries, reaching almost 50%, and resistance to clarithromycin is as high as 30% and is still increasing, contributing to the failure of first-line therapy in approximately 70% of patients. Moreover, the introduction of levofloxacin to eradication therapy of H. pylori infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 34 publications
(59 reference statements)
2
30
3
Order By: Relevance
“…In our study, A2143G was the most common type of mutation in strains. This finding verified previous studies by other researchers [7,26]. Furthermore, 9.5% of clarithromycin-resistant H. pylori strains lacked the studied mutations.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, A2143G was the most common type of mutation in strains. This finding verified previous studies by other researchers [7,26]. Furthermore, 9.5% of clarithromycin-resistant H. pylori strains lacked the studied mutations.…”
Section: Discussionsupporting
confidence: 92%
“…23 H. pylori strains were found to carry A2143G, A2142G, A2147G and A2146G mutations that can lead to clarithromycin-resistance in Africa, Asia, South America, Europe and North America. [24][25][26][27][28][29][30] The T2183C and A2223G transformations have been frequently found to be the cause of observed clarithromycin resistance in Asian countries than those in Europe and North America, 31 but not be observed in our study. In addition to these mutations, other mutations in different positions have been found in other parts of the world to confer clarithromycin resistance in H. pylori strains (T2182C, T2190C, C2195T, A2223G, G2141A, C2694A, G2224A, C2245T, T2289C).…”
Section: Discussioncontrasting
confidence: 62%
“…Binkowska et al reported that the most common mutation presented in 40% of H. pylori strains resistant to levofloxacin was a change at position 91 of gyrA in children. 25 De Palma et al reported that resistance of levofloxacin was due to substitution at position 87 (K,I) and 91 (G,N,A) of gyrA QRDR in the 92.8% of the resistant isolates. 40 Miftahussurur et al reported that mutations at Asn-87 and/or Asp-91 were predominantly in levofloxacinresistant strains, and the gyrB mutation had a steady relationship with gyrA 87-91 mutations.…”
Section: Discussionmentioning
confidence: 99%
“…We then isolated bacteria DNA from patient gut biopsy samples and successfully distinguished the antibiotic resistance genotype from another closely matched synthetic wild type sequence ( Figure 3C). Importantly, this procedure takes a few hours from obtaining sample to diagnosing the variant, a significant improvement over existing regimens which rely on antimicrobial susceptibility tests that can take several days to complete 27 .…”
Section: Genotyping Carrier Individuals With Heterozygosity Though Nomentioning
confidence: 99%